2010
DOI: 10.4314/gjes.v8i1.50817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crude oil on the gastropod, tympanotomus fuscata in the Cross River Estuary, south-east Nigeria

Abstract: Edible periwinkle, Tympanotonus fuscata, was collected from the Cross River estuary, allowed to acclimate to laboratory conditions for a week and then exposed to Nigerian light crude oil at different concentrations of 50ml, 100ml, and 150ml per litre of water for a period of 96 hours. Mud (80g) was added to all the 4-litre aquaria used for the experiment. The oil was thoroughly mixed with the estuarine water by stirring vigorously. During the 4-days experimental period, most of the specimens suffered suffocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…As deposit feeders, periwinkles may have incorporated part of the dissolved components of the kerosene into its tissues [16] which eventually may have altered the normal body physiology and biochemistry of the periwinkle, thereby leading to death. The mortality pattern in this study is in accordance with the findings of [4,13,16] who observed that mortality of periwinkle from petroleum products depends on the concentration of the products and duration of exposure. The kerosene prevents gaseous exchange between the respiratory organs and the affector sites thereby hindering the oxygen changing capacity of the periwinkle which lead to death [17].…”
Section: Discussionmentioning
confidence: 99%
“…As deposit feeders, periwinkles may have incorporated part of the dissolved components of the kerosene into its tissues [16] which eventually may have altered the normal body physiology and biochemistry of the periwinkle, thereby leading to death. The mortality pattern in this study is in accordance with the findings of [4,13,16] who observed that mortality of periwinkle from petroleum products depends on the concentration of the products and duration of exposure. The kerosene prevents gaseous exchange between the respiratory organs and the affector sites thereby hindering the oxygen changing capacity of the periwinkle which lead to death [17].…”
Section: Discussionmentioning
confidence: 99%